Optimizing the performance of P3HT-based photodetector by tuning the composition of OXCBA / Syaza Nafisah Hisamuddin - Syaza Nafisah , Hisamuddin (2021)
Organic photodetectors (OPDs) have shown high responsivity and detectivity limits with fast response speed that are matched with commercially available inorganic photodetectors. The feasibility to tune the spectral response of the organic material and flexibility to use on curve substrate also give the advantage of using organic materials in the fabrication of OPDs. Nevertheless, there are still many challenges that need to be addressed to achieve a greater performance of an OPD device. In this work, the performance of organic-based photodetectors using poly(3-hexylthiophene) (P3HT) and o-xylenyl-C60-bisadduct (OXCBA) as the donor and acceptor material, respectively, is reported aiming to improve the performance of P3HT-based OPD device. Four different ratios of 1:0.25, 1:0.50, 1:1.00 and 1:1.50 of P3HT:OXCBA binary blended thin films are prepared using spin-coating technique and used as photoactive layers. The elemental composition and electronic properties of the materials are characterized using X-ray Photon Spectroscopy (XPS) and Ultraviolet Photon Spectroscopy (UPS). The optical properties of the thin films are characterized using Ultraviolet-visible (UV-vis) spectroscopy and the electrical performance for all ratios are characterized using currentvoltage (I-V) measurement. Further, two blend ratios that show the best and the worst performance are characterized using Photoluminescence (PL) Spectroscopy, Atomic Force Microscopy, Raman Spectroscopy. It was found that the combination of P3HT and OXCBA demonstrates a wide spectral range of light absorption which covers the valley that has low light absorption, with the ratio of 1:0.50 demonstrates the best performance. The OPD devices with ratio 1:0.25 to 1:1.50 shows high photocurrent density (Jph) from 8.09 mA/cm2 to 25.27 mA/cm2. Optimizing the ratio of photoactive layers dramatically enhances the performance of OPDs, with the rise and decay time of 445 and 309 ms, respectively, recorded from 1:0.50 ratio. The optimized device has achieved high responsivity of 252.69 mA/W and specific detectivity of 1.85x1010 Jones at -1 V, and has shown good stability for over 336 hours. Aside from that, external quantum efficiency (EQE) of 52.77% and low surface roughness of 0.596 nm are obtained from the 1:0.50 P3HT: OXCBA device. These results imply a high potential of P3HT:OXCBA blend in the application of a photodetector.